2004
DOI: 10.1158/1078-0432.ccr-050003
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and Partial Nephrectomy

Abstract: Radical nephrectomy is the gold standard curative operation for patients with localized renal cell carcinoma (RCC). Since its introduction in 1990, laparoscopic radical nephrectomy is being increasingly done at numerous institutions worldwide. In the hands of experienced laparoscopic urological surgeons and with adherence to established principles of open radical nephrectomy, laparoscopic radical nephrectomy is now a standard of care for patients with T 1-3a N 0 M 0 RCC. Intermediate-term outcome data indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 21 publications
1
50
0
4
Order By: Relevance
“…[2][3][4][5][6] Easier convalescence [7][8][9][10] and equivalent cancer control 10 have established laparoscopy as an alternative standard of care for most patients who undergo radical nephrectomy. 1,2,4,11,12 In synchronicity with the gradual dissemination of laparoscopic radical nephrectomy, 2,4 multiple investigators reported that, for selected patients with smaller renal tumors, partial nephrectomy yields oncologic outcomes that are indistinguishable from the outcomes achieved by radical excision. [13][14][15] Partial nephrectomy also preserves long-term renal function 16,17 while reducing over-treatment of patients with benign 18 or clinically indolent 19 tumors.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Easier convalescence [7][8][9][10] and equivalent cancer control 10 have established laparoscopy as an alternative standard of care for most patients who undergo radical nephrectomy. 1,2,4,11,12 In synchronicity with the gradual dissemination of laparoscopic radical nephrectomy, 2,4 multiple investigators reported that, for selected patients with smaller renal tumors, partial nephrectomy yields oncologic outcomes that are indistinguishable from the outcomes achieved by radical excision. [13][14][15] Partial nephrectomy also preserves long-term renal function 16,17 while reducing over-treatment of patients with benign 18 or clinically indolent 19 tumors.…”
mentioning
confidence: 99%
“…Partial nephrectomy provides recurrence-free and longterm survival rates similar to radical nephrectomy for tumours < 4 cm in diameter. [8][9][10] Further, partial nephrectomy is associated with a lower risk of longterm renal dysfunction. 11 There is preliminary experience with HIFU (high intensity focussed ultrasound), but probe ablation by RFA and cryotherapy has been extensively reported with promising early results in terms of efficacy and side effects.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Some have questioned its benefits [28][29][30][31] while others have used laparoscopy for IVC tumor thrombi using open incisions for tumor thrombectomy after laparoscopic mobilization and dissection [32][33][34] or pure laparoscopy with hand assistance for the thrombectomy only [35]. Single case reports have also been described using hand-assisted or pure laparoscopy for short thrombi [36,37], recently few case reports and one case series of robotic IVC thrombectomy has been reported in the literature [38].We await results of larger series since robotic and laparoscopic IVC tumor thrombectomy remain a challenging procedure and should not be embarked on lightly and hence open surgery remains the predominant method for addressing RCC involving the IVC.…”
Section: Minimal Invasive Techniquesmentioning
confidence: 99%